Türkçe Öğretmeni Adaylarının Dinleme ve Okuma Öz Yeterlikleri İle Öğrenme Stillerinin İncelenmesi - Gerez Taşgın, Fatma (Muş Alparslan Üniversitesi, 2019)
Theaim of this study is to examine the listening and reading self-efficacy levelsof Turkish preservice teachers and their learning styles. The study adopted asurvey research methodology. The population of the study consisted of Turkishpre-service teachers studying at Faculty of Education of a state university.Since the entire study population could be reached, no sampling was chosen. Inthis study, it has been concluded that there are significant differences insome of the self-efficacy competencies of Turkish preservice teachers in termsof gender, grade, high school type that they graduated, and weighted gradepoint average. It has also been found that the self-efficacy competencies ofTurkish pre-service teachers are at the “I agree” level in total. It has beendetermined that the majority of the Turkish pre-service teachers have alearning style of “Diverging”,   but thereis no difference between the learning styles of preservice teachers and theirlistening and reading self-efficacy.

Buaraştırmanın amacı, Türkçe öğretmeni adaylarının dinleme ve okuma özyeterlikleri ile öğrenme stillerini incelemektir. Bu çalışma, tarama türündebir araştırmadır. Araştırmanın evrenini bir devlet üniversitesinin eğitimfakültesinde öğrenim gören Türkçe öğretmeni adayları oluşturmaktadır. Çalışmaevreninin tamamına ulaşıldığı için herhangi bir örneklem seçme yolunagidilmemiştir. Bu araştırmada Türkçe öğretmeni adaylarının dinleme ve okuma özyeterliklerinin, genel toplamda “Katılıyorum” düzeyinde olduğu, cinsiyet, sınıf, mezun olunan lise türü ve ağırlıklı genel not ortalaması bakımından heriki temel dil becerisine yönelik öz yeterliklerin bazılarında anlamlıfarklılıklar olduğu sonucuna ulaşılmıştır. Ayrıca Türkçe öğretmeni adaylarınınbüyük bir bölümünün “Değiştiren” öğrenme stiline sahip olduğu, öğretmenadaylarının sahip oldukları öğrenme stilleri ile dinleme ve okuma öz yeterlikleriarasında ise herhangi bir farklılaşma olmadığı tespit edilmiştir.
Examining Listening and the Reading Self-Efficacy Levels of Turkish Preservice Teachers andTheir Learning Styles
anemon
Keywords: Listening; Reading; Self-efficacy; Learning styles; Dinleme; Okuma; Öz Yeterlik; Öğrenme Stili